Families' perspectives of participation in patient care in an adult intensive care unit: A qualitative study. Issue 4 (July 2020) - Wong, Pauline; Redley, Bernice; Digby, Robin; Correya, Anu; Bucknall, Tracey
Abstract: Background: When a relative is admitted to the intensive care unit (ICU), stress, anxiety, and failure to cope may place families, and the patient, at risk for adverse psychological outcomes. Family participation in patient care may improve patient and family outcomes. However, to date, little is known about how families perceive and participate in patient care in ICU, and there is limited research to guide clinicians about supporting family participation in this context. Objective: To describe family perspectives of participation in patient care in adult ICU. Methods: Using a qualitative design, observation and interview data were collected from a convenience sample of 30 family members in the ICU at two metropolitan hospitals in Melbourne, Australia. An independent third party was used to recruit potential participants. Naturalistic observations and semi-structured interviews explored families' actions and perceptions of participation. Data were integrated and subject to thematic analyses. Findings: The major theme Families as part of the healthcare team reflected family perspectives of their own significant contribution to supporting their relative's recovery while they were in ICU. Families' perception of their participation in patient care was characterised by three sub-themes: 1) Motivators for family participation; 2) Family roles during recovery; and 3) Influences on family participation. Families' perceived reassurance and companionship as important contributions to patient care. Conclusion: Families perceived their contribution to the patient's psychosocial and emotional well-being to be one of the most important aspects of participation. Nevertheless, their role in the healthcare team was influenced by several motivational factors. Results of this study can inform further research to test the effectiveness of clinical practice and educational interventions aligned with family preferences to promote participation and enhance patient and family-centered care in ICU.